A Study on Work Related Attitudes of Generation Z at Workplace in India: Exploring the Impact of Generation Z on the Changing Workplace Culture (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study has been undertaken to understand that there has been a noticeable change in the way work and workplace culture is perceived, there has been a paradigm shift in how businesses have grown, and similarly, human resources have gone through evolutionary change, the days have gone by when all employees aspired to be paid on time and have a stable job for a lifetime. One of the major demographic phenomenon recorded in the present time is represented by the aging of the Indian population and consequently, this issue has several implications for organizational human resource management. As the current generation grows older, the effect of Generation Z is extremely vital as they might influence and run companies from 2020 onwards, managers must face a range of generational differences between their workers. Managers must face a number of generational differences among their workers. As a result of this proposed study, the understanding of the ideal workplace generation Z and its job goals and ambitions will be emphasized.